Copyright Infringement Crime in Islamic Criminal Law - Muhammad Alwin Abdillah; Nairazi; Lina Agustina (IAIN Langsa, 2022)
This research tells about the Crime of Copyright Infringement in Islamic Criminal Law. Copyright in contemporary Islamic scholarship is known as haq Al-ibtikar. From the word there are two sets of words namely had and al-ibtikar. The definition of had is a specialty owned by a person or group of people over something. While in etymology al-ibtikar comes from Arabic in the form of isim mashdar, al-ibtikar itself means to create. Islam recognizes intellectual property rights and protects them from the hands of destroyers and robbers. Whoever robs it is obliged to pay compensation. Intellectual property rights in Islam are classified as property. Therefore, stealing someone's intellectual property rights applies to the law of theft. Islam forbids theft in its various types and is obliged to return the stolen goods. Not only that, Islam also imposes hadd punishment for perpetrators of sariqah (theft) and ta'zir punishment for perpetrators of ghasb (mugging). This is one of the clear proofs that Islam is very protective and safeguards one's property.